Antecedents and Outcomes of Network Involvement in the Internationalization Process: A Case of SMEs from the USA, China, and Russia - Mikhailitchenko, Andrey (Organizations and Markets in Emerging Economies, 2021)
The internationalization processes of small and medium-sized enterprises (SMEs) differ across economic and cultural environments. Creating an operationalizable and predictive framework to explain them has long been a challenging research task. This task is particularly relevant in an era of reconfiguration of globalization, which directly affects the small business sector. This study proposes a model which includes networking, attitudinal, cultural, and environmental factors as antecedents of the degree of SME internationalization. We collected data and tested this model in three distinct cultural environments: the USA, China, and Russia. The results suggest that attitudinal characteristics of managers, such as global mindset and relationship commitment, condition SMEs network involvement. The influence of network involvement on the degree of SMEs internationalization becomes stronger with increasing environmental turbulence. This study’s findings have practical implications for businesses operating in different countries, as well as governmental organizations and educational institutions.